Implementasi Ambiguitas Konflik Program Kelurahan Bersih Narkoba Setonopande dalam Rangka Pencegahan, Pemberantasan, Penyalahgunaan, dan Peredaran Narkoba - Kurniawan, Yoga; Hanafi, Imam; Said, Moh. (Jurnal Ilmiah Administrasi Publik, 2024)
This research was conducted to describe and explain the implementation of the Clean Drug Village Program in Setonopande Village, Kediri City in the perspective of Conflict Ambiguity Implementation and find out what are the most supportive and inhibiting factors in the implementation of this program. This research uses Qualitative methods with a Descriptive approach, and uses NVIVO in data processing. Kelurahan Bersih Narkoba is a program of the National Narcotics Agency in collaboration with local governments in the context of preventing, eradicating, abusing, and distributing drugs in the smallest scope, namely villages, this is done to reduce the high number of national drug trafficking. The results of this study indicate that the implementation of the Setonopande Clean Drug Village is going well, this is indicated by the fulfillment of the Five Precise Indicators of Program/Policy Implementation which contains the accuracy of the policy, implementation, target, environment, and the accuracy of the process, on the other hand there are still findings of implementation that are still less precise and can be improved in the future, such as communication between implementers, making clear and specific regulations, and allocating a special budget for this program. This research is expected to provide suggestions to Setonopande Village for the next implementation, and other regions can adopt the success of the implementation of this program.